Long non-coding RNA H19 enhances the pro-apoptotic activity of ITF2357 (a histone deacetylase inhibitor) in colorectal cancer cells - Zichittella, Chiara; Loria, Marco; Celesia, Adriana; Di Liberto, Diana; Corrado, Chiara; Alessandro, Riccardo; Emanuele, Sonia; Conigliaro, Alice (Frontiers in Pharmacology, 2023)
Introduction: Long non-coding RNA H19 (lncH19) is highly expressed in Colorectal cancer (CRC) and plays critical roles in tumour development, proliferation, metastasis, and drug resistance. Indeed, the expression of lncH19 usually affects the outcome of chemotherapy, endocrine therapy, and targeted therapy. ITF2357 (Givinostat) is a Histone deacetylase inhibitor that revealed a significant anti-tumour action by inducing apoptosis in different tumour models including leukaemia, melanoma, and glioblastoma. However, no data are present in the literature regarding the use of this compound for CRC treatment. Here we investigate the role of lncH19 in ITF2357-induced apoptosis in CRC cells. Methods: HCT-116 CRC cell line was stably silenced for H19 to investigate the role of the lnc in ITF2357-induced cell death. Cell viability assays and flow cytometric analyses were performed to assess the antiproliferative and pro-apoptotic effects of ITF2357 in CRC cell lines silenced or not for lncH19. RT-PCR and western blot were used to study the effects of ITF2357 on autophagy and apoptosis markers. Finally, bioinformatics analyses were used to identify miRNAs targeting pro-apoptotic factors that can be sponged by lncH19. Results: ITF2357 increased the expression levels of H19 and reduced HCT-116 cell viability inducing apoptosis, as demonstrated by the increase in annexin-V positivity, caspase 3 cleavage and Poly ADP-Ribose Polymerase (PARP-1) degradation. Interestingly, the apoptotic effect of ITF2357 was much less evident in lncH19-silenced cells. We showed that lncH19 was functional to the pro-apoptotic activity of the drug by stabilizing TP53 and its transcriptional targets NOXA and PUMA. ITF2357 also induced autophagy in CRC cells that was interpreted as a pro-survival response not correlated with lncH19 expression. Furthermore, ITF2357 induced apoptosis in 5-Fluorouracil-resistant HCT-116 cells that express high levels of lncH19. Conclusions: This study shows that lncH19 expression contributes to ITF2357-induced apoptosis by stabilizing TP53. Overall, we suggest that lncH19 expression may be exploited to favour HDACi-induced cell death and to overcome 5-Fluorouracil chemoresistance.